Synthetic Naphthofuranquinone Derivatives Are Effective in Eliminating Drug-Resistant Candida albicans in Hyphal, Biofilm, and Intracellular Forms: An Application for Skin-Infection Treatment - Fang, Jia-You; Tang, Kai-Wei; Yang, Sien-Hung; Alalaiwe, Ahmed; Yang, Yu-Ching; Tseng, Chih-Hua; Yang, Shih-Chun (Frontiers in Microbiology, 2020)
Candida albicans is the most common cause of fungal infection. The emergence of drug resistance leads to the need for novel antifungal agents. We aimed to design naphthofuranquinone analogs to treat drug-resistant C. albicans for topical application on cutaneous candidiasis. The time-killing response, agar diffusion, and live/dead assay of the antifungal activity were estimated against 5-fluorocytosine (5-FC)- or fluconazole-resistant strains. A total of 14 naphthofuranquinones were compared for their antifungal potency. The lead compounds with hydroxyimino (TCH-1140) or O-acetyl oxime (TCH-1142) moieties were the most active agents identified, showing a minimum inhibitory concentration (MIC) of 1.5 and 1.2 μM, respectively. Both compounds were superior to 5-FC and fluconazole for killing planktonic fungi. Naphthofuranquinones efficiently diminished the microbes inside and outside the biofilm. TCH-1140 and TCH-1142 were delivered into C. albicans-infected keratinocytes to eradicate intracellular fungi. The compounds did not reduce the C. albicans burden inside the macrophages, but the naphthofuranquinones promoted the transition of fungi from the virulent hypha form to the yeast form. In the in vivo skin mycosis mouse model, topically applied 5-FC and TCH-1140 reduced the C. albicans load from 1.5 x 106 to 5.4 x 105 and 1.4 x 105 CFU, respectively. The infected abscess diameter was significantly decreased by TCH-1140 (3‒4 mm) as compared to the control (8 mm). The disintegrated skin-barrier function induced by the fungi was recovered to the baseline by the compound. The data support the potential of TCH-1140 as a topical agent for treating drug-resistant C. albicans infection without causing skin irritation.